A Graph Theoretic Framework for Integrated and Co‐optimized Power System Planning. Issue 1 (13th September 2016) - Khiyami, Abdulaziz; Ishimatsu, Takuto; Alfaris, Anas; de Weck, Olivier L.
Abstract: Increased interest in renewable generation has made siting constraints more prominent in power system planning. In addition the power system is increasingly being considered as one of many coupled critical infrastructure systems in nexus' such as the food‐energy‐water nexus and the gas‐electricity nexus. This paper describes a power system planning approach within a graph theoretic framework that allows for the handling of the geographical aspects of electricity production and distribution as well as the interaction of electricity network with other critical infrastructures.